Approach to scorpion stings in pregnancy: A retrospective case series and literature review - Sinan Ates; Mahmut Alp Karahan; Nuray Altay; Kazim Akelci; Nagehan Ikiz; Bulent Guzel; Mandeley Wilhelmina Ozer; Haci Durmus Yilmaz (Elsevier, 2018)
Abstracts: Objective: Scorpion stings remain a serious health problem in many parts of the world. There is very limited information regarding the effects of therapies delivered for scorpion stings in pregnant women on the mother and fetus. They can cause acute conditions such as fetal loss, preterm delivery, or placental abnormalities and can also result in other conditions that may have an effect on the baby in the long term. Materials and methods: In this study the medical records of 24 pregnant women who were admitted to the emergency room at Suruç State Hospital due to scorpion stings between January 1, 2013 and January 1, 2014 were retrospectively reviewed. Age, gestational week, monthly distribution of the cases, type of delivery, status of the fetus, affected body sites, and local and systemic findings were evaluated. The clinical severity of each case was assessed using Abroug's classification. A fetal biophysical profile test was administered in pregnant women above 24 weeks of gestation. The newborns underwent follow-up for mental and motor functions in the pediatric department at three-month intervals for 12 months. Results: 24 patients, with a mean age of 26.1 ± 2.4 years, were included in the study. The most common region stung by scorpions was Lower extremity (58.3%). The most common symptom occurred in cases was immediate localized pain (58%). In terms of gestational age, 41.6% of scorpion sting were within the third trimester. Biophysical profile scores were 8 and above. Only symptomatic treatment, without use of anti-venom, was done to all the patients in this study. And neither death nor major sequel happened. Conclusion: Scorpion stings during pregnancy may not have significant adverse effects on the fetus and the mother. Decisions regarding the use of anti-venom in pregnant women should be considered carefully when only limited safety information, especially in those patients with only local symptoms. Keywords: Emergency department, Fetus, Pregnancy, Scorpion stings